Giant serous cystadenoma - Fernández, Víctor (2015)
Ovarian serous cystadenoma is a type of tumor derived from superficial (celomic) epithelitun constituted by cystic areas. Reason for these ovarian tumors predominance is a mystery. We report one case presenting in a patient transferred to our medical center because of a two months evolution large increase in abdominal size. Diagnosis was suspected by pelvic ultrasound, a giant 22 kg tumor was found during surgery and diagnosis was confirmed by pathology.